Retrospective and new records of ticks (Acari: Argasidae, Ixodidae) from the state of Maranhão, an Amazon-Cerrado transition area of Brazil - Costa, Francisco Borges; Martins, Thiago Fernandes; Muñoz-Leal, Sebastián; de Azevedo Serpa, Maria Carolina; Ogrzewalska, Maria; Luz, Hermes Ribeiro; Barros-Battesti, Darci Moraes [UNESP]; de Carvalho Mesquita, Eric Takashi Kamakura; da Costa, Andréa Pereira; de Maria Seabra Nogueira, Rita; Labruna, Marcelo Bahia (Elsevier, 2020)
The Brazilian state of Maranhão is located in a transition area of the Amazon and Cerrado biomes, where there is a rich fauna of vertebrates. This study aimed to update the list of the ticks occurring in Maranhão, through a compilation of literature records and examination of three tick collections, plus the addition of unpublished collections of ticks from road-killed animals during recent years. Our results indicate that the tick fauna of Maranhão includes 26 species: seven in the family Argasidae (Antricola guglielmonei, Argas miniatus, Ornithodoros cavernicolous, Ornithodoros hasei, Ornithodoros mimon, Ornithodoros rietcorreai and Ornithodoros rudis); and 19 in the family Ixodidae (Amblyomma auricularium-provisional, Amblyomma cajennense sensu stricto, Amblyomma calcaratum, Amblyomma dissimile, Amblyomma geayi, Amblyomma longirostre, Amblyomma naponense, Amblyomma nodosum, Amblyomma oblongoguttatum, Amblyomma ovale, Amblyomma parvum, Amblyomma rotundatum, Amblyomma sculptum, Amblyomma triste, Dermacentor nitens, Ixodes luciae, Haemaphysalis juxtakochi, Rhipicephalus microplus, and Rhipicephalus sanguineus sensu lato). Eleven of the above species are reported for the first time in Maranhão. We consider previous reports of Ornithodoros talaje and Amblyomma pseudoconcolor in Maranhão as misidentification with O. hasei and A. auricularium, respectively. Until 1958, only 11 tick species were reported in Maranhão, with no additional reports until 2009. During 2010–2019, 15 additional species were reported. We also highlight the importance of ticks for public and veterinary health in Maranhão.
Keywords: Amblyomma; Haemaphysalis; Hosts; Ixodes; Ornithodoros; Tick fauna